Friction Welding of AISI 304 and AISI 1021 Dissimilar Steels at 1600RPM - Handa, Amit; Chawla, Vikas (Asian Review of Mechanical Engineering, 2013)
Friction welding is a solid state joining process which is extensively used due to its advantages such as low heat input, ability to join dissimilar materials and environment friendliness. Friction welding can be used to join different kinds of materials which cannot be welded by conventional fusion welding processes. The rotational speed and the axial pressures are the important parameters that play the major role in determining the strength of the joint. In this study an attempt was made to join austenitic stainless steel (AISI 304) with low alloy steel (AISI 1021) at 1600 rpm and at different axial pressures and then determining the strength of the joint by means of mechanical properties such as tensile strength, torsional strength, impact strength and micro hardness. The tensile tested specimens were also subjected to SEM analysis to determine the failure pattern of the specimens